Performance evaluation of phase change material integration in buildings using novel non-dimensional performance parameters for different cities and months in India. (October 2021) - Arun Prakash, S.; Gunadevan, D.; Arivazhagan, R.; Sheeja, R.; Antony Aroul Raj, V.; Velraj, R.
Highlights: Two non-dimensional parameters were proposed to calculate the effectiveness of PCM integration. Non-dimensional parameters captured the latitude effects of PCM integration in the building. The analysis results were useful for pre-installation studies of PCM integration in the building. Abstract: In recent years, Phase Change Material (PCM) has been used in the thermal management of buildings for reducing the heat entry through the building envelope, and to maintain comfort. The effectiveness of PCM integration in a building would be high, in locations where diurnal ambient temperature variation is high. Selection of PCM with correct phase change temperature range for building envelope is a challenging task for building engineers, owing to the complex transient behaviour of PCM during its charging and discharging cycles. There is a need for a user-friendly numerical simulation tool for the selection of PCM with maximum effectiveness for a building at a particular location, at less cost and time. Also, there is a requirement for a non-dimensional PCM performance parameter to compare the thermal performance of a building with and without PCM integration. In current research work, a numerical tool has been developed using MATLAB software for performing thermal analysis of a building integrated with PCM in walls and roof. Further, year-round performance studies were carried out for measuring the effectiveness of PCM for selected geometry at different locations. Two novel non-dimensional parameters, namely, PCM performance parameter (PPP) and percentage drop in relative indoor temperature integral (PDR) have been introduced in this present work to determine the effectiveness of PCM integration in a building. Simulation has been carried out for a building model with and without PCM in five, cities in different geographical locations of India. Analysis has been carried out by selecting PCM with a suitable temperature range based on local climate for a particular time of the year. The concluding results have shown the usefulness of this user-friendly simulation tool and the PCM performance parameters in evaluating the performance of PCM integrated buildings at any location and time of the year. The developed numerical tool is useful for the selection of correct PCM for a location and time of the year. Also, the non-dimensional parameters proposed captured the latitude effects of a building integrated with PCM in walls and roof.